2009
DOI: 10.1021/ac901420u
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Disposable Microfluidic Biochip for Multiparameter Cell Population Measurements

Abstract: An under recognized cause of preventable mortality is healthcare-associated (nosocomial) infections such as biofilms found on implants and catheters. About 5% of U.S. and E.U. patients acquire nosocomial infections leading to prolonged hospitalization, increased patient suffering, and mortality rates. To date, no satisfactory solutions are available to monitor biofilm formation under near-native conditions. As a consequence, in the present work, we report the development of a disposable microfluidic biochip ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Gottschamel et al . found that contactless bioimpedance measurements are particularly sensitive toward capacitive changes during biofilm formation and maturation 58 . Kim et al .…”
Section: Introductionmentioning
confidence: 99%
“…Gottschamel et al . found that contactless bioimpedance measurements are particularly sensitive toward capacitive changes during biofilm formation and maturation 58 . Kim et al .…”
Section: Introductionmentioning
confidence: 99%
“…Junil 2012). In bioelectrochemical systems, either the direct interaction between microorganisms and electrodes can be used, or the microbe-electrode communication can be induced with natural (Wang, Tsujimura et al 2007) or artificial redox mediators (Roller SD 1984;Heiskanen A 2004;Gottschamel, Richter et al 2009). Electrochemical detection methods that are based on redox mediators are applicable when the reduced electron acceptor can be oxidized at electrodes (K. Junil 2012;Congdon, Feldberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gottschamel et al [88] developed a disposable microfluidics biochip for multiparameter Candida albicans population measurements, which can monitor Candida albicans growth rates and metabolic activities by simultaneous bioimpedance spectroscopy and amperometric measurements. Zhu et al [92] used fluidic electrodes to fabricate a microfluidics device for detecting bacterial cells in deionized water suspensions with a detection limit of 10 3 cfu·mL −1 .…”
Section: Microfluidics Techniquesmentioning
confidence: 99%